Foods provided to children in family day care: an observational study. Issue 11 (6th August 2021) - Kerr, Erin M; Kelly, Bridget; Hammersley, Megan L; Hernandez, Lara; Norman, Jennifer; Furber, Susan; Vuong, Cecilia; Ryan, Sarah; Wardle, Karen; Okely, AD
Abstract: Objective: To assess the quality and quantity of foods and beverages provided to children aged 0–5 years in family day care and identify structural and sociodemographic factors associated with the nutritional quality of food provided. Design: A cross-sectional study measured the food and beverages provided to children using weighed food records. The number of serves from different food groups was calculated according to the Australian Guide to Healthy Eating, and a healthy food provision index score was created. Associations between structural and sociodemographic factors and healthy food provision index scores were analysed using linear mixed models. Setting: Family day care services in two large geographic areas in New South Wales, Australia. Participants: One hundred and four children in thirty-three family day care services. Results: During attendance at childcare, most children met recommended servings of fruit but not dairy, vegetables, lean meat and meat alternatives and wholegrains. Discretionary foods exceeded recommendations. Children's age, socio-economic status and the type of main meal provided were significantly associated with the healthy food provision index score. Conclusions: Foods provided to children in family day care are aligned with dietary recommendations for fruit but not vegetables, dairy, lean meat and meat alternatives, wholegrains or discretionary foods. Interventions to promote healthy eating are needed to support families and educators to improve the nutritional quality of food provided to children.